Penninic ophiolites at the eastern margin of the Eisenberg-group (Felsőcsatár, W-Hungary) - Kotsis T. (Acta mineralogica-petrographica, 1986)
At the Eastern termination of the Alps there are various greenstones of basaltic origin, ullramafitites and a meta-ultrabasic rocks exposed in the tectonic windows of the Eisenberg-Group. The paper gives detailed description of the mineralogy and mineral chemistry of this rock suite.